THE EFFECT OF SILVER NANOPARTICLE SOLUTION TOWARD THE OUTPUT VOLTAGE AND ELECTRIC CURRENT IN THE USED DRY ACCUMULATOR - Johan Haryanto, Wipsar Sunu Brams Dwandaru (Prodi Fisika, Departemen Pendidikan Fisika, 2018)
This study aims to i) to know the effect of H2SO4 electrolyte solution concentration toward the output voltage and electric current of the used dry accumulator after added 3 mM nanosilver solution ii) to find out the concentration of H2SO4 electrolyte solution which gives maximal influence toward the output voltage and electric current of the used dry accumulator after added 3 mM nanosilver solution, iii) to know the ratio of output voltage and electric current of the used dry accumulator which added nanosilver + H2SO4 electrolyte solution with variations of concentration and without nanosilver + H2SO4 electrolyte solution. This research begin by synthesizing silver nanoparticles concentrated 3 mM for each research performed. Next, tested the quality of the silver nanoparticle solution with the UV-Vis Spectrophotometer test. Then, make a solution of electrolyte H2SO4 with variation of concentration that is 50%, 40%, 30%, 20%, and 10%. Next, mix 1 mL of each H2SO4 concentration with 3 mL silver nanoparticle solution 3 mM and test the solution with a UV-Vis Spectrophotometer test. Then, 4 mL of the mixed solution is added to the used dry accumulator. Measurements of the output voltage and electric current of the used dry accumulator are carried out in a good quality solution until four hours with the use of LED lights. Based on the results obtained, it is known that the concentration of H2SO4 electrolyte solution has an effect on the output voltage and electric current of the used dry accumulator which contains H2SO4 solution and silver nanoparticle solution 3 mM. The concentration of H2SO4 electrolyte solution which gives maximal effect to the output voltage of the used dry accumulator is H2SO4 electrolyte solution which has 50% concentration. The concentration of H2SO4 electrolyte solution which gives maximal effect to the electric current of the used dry accumulator is H2SO4 electrolyte solution which has 50% concentration. Keywords: nano, silver nanoparticle, used dry accumulator, sulfuric acid, voltage and current